Vat photopolymerization of unsaturated polyesters utilizing a polymerizable ionic liquid as a non-volatile reactive diluent. (3rd May 2021) - White, B. Tyler; Meenakshisundaram, Viswanath; Feller, Keyton D.; Williams, Christopher B.; Long, Timothy E.
Abstract: Unsaturated polyester resins (UPRs) enjoy numerous applications as structural adhesives in glass fiber laminates, concrete flooring, and masonry repair. Typically, UPRs consist of unsaturated polyester (UPE) oligomers with up to 50 wt% of a reactive diluent such as styrene. The ability of these resins to cure rapidly upon UV irradiation, in conjunction with a photoinitiator, enables vat photopolymerization (VP) 3D printing. However, the volatility and toxicity of styrene limits the use of traditional UPRs for VP. This report describes a nonvolatile ionic liquid reactive diluent for UPRs, which, in combination with the unreactive diluent dimethoxyethane, produce resins suitable for VP. Photorheological experiments help guide resin design for VP based on a series of synthesized UPEs and PIL concentrations. Photocured networks exhibit increasing degradation temperatures with increasing PIL incorporation from 215 to 279 °C. VP of a selected UPR composition demonstrated the ability to form self-supporting, geometrically complex 3D printed structures, suggesting the opportunity to utilize a common industrial feedstock as a component of a novel VP resin system. Dried and unextracted 3D printed test specimens exhibit ionic conductivities spanning from 10 −8 to 10 −5 S cm −1 between 60 and 150 °C, which indicate a potential additional attribute for 3D printed UPE parts. Graphical abstract: Image 1 Highlights: Phosphonium IL serves as a reactive diluent in unsaturated polyester resins. Photorheology screens resin compositions for vat photopolymerization 3D printing. Vat photopolymerization yields 3D printed structures from the low-volatility resin. IL monomer imparts ionic conductivity and thermal stability in printed parts.